2020
DOI: 10.1086/702996
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Education on Financial Outcomes: Evidence from Kenya

Abstract: We study the effects of education on the financial outcomes of youth using Kenya's introduction of Free Primary Education (FPE) in 2003 as an exogenous shock to schooling. Our identification strategy compares changes across cohorts, and across regions with differing levels of pre-FPE enrollment. We find that FPE is associated with increases in educational attainment and increased use of formal financial services, particularly through mobile banking. Examining potential mechanisms, we find increases in employme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
(38 reference statements)
0
14
1
Order By: Relevance
“…At least some individuals in the developing world seem to have the potential to do this on their own: recent studies have found very large, on the order of 5-30 percent per month, marginal returns to capital among microenterprises in contexts as varied as Sri Lanka, Ghana, India, Mexico, and Uganda. 1 Other researchers have documented individuals regularly revolving debt at interest rates as high as 10 percent per day (Aleem 1990;Ananth, Karlan, and Mullainathan 2007;Banerjee and Duflo 2007), while Schofield (2014) finds a 75-225 percent (financial) return to caloric consumption in India. When returns are this high, modest changes in investment behavior can lead to substantial gains in longer-run economic wellbeing; yet existing research provides little guidance as to how (or whether) such behavior change can be activated.…”
mentioning
confidence: 99%
“…At least some individuals in the developing world seem to have the potential to do this on their own: recent studies have found very large, on the order of 5-30 percent per month, marginal returns to capital among microenterprises in contexts as varied as Sri Lanka, Ghana, India, Mexico, and Uganda. 1 Other researchers have documented individuals regularly revolving debt at interest rates as high as 10 percent per day (Aleem 1990;Ananth, Karlan, and Mullainathan 2007;Banerjee and Duflo 2007), while Schofield (2014) finds a 75-225 percent (financial) return to caloric consumption in India. When returns are this high, modest changes in investment behavior can lead to substantial gains in longer-run economic wellbeing; yet existing research provides little guidance as to how (or whether) such behavior change can be activated.…”
mentioning
confidence: 99%
“…Therefore, our intergenerational analysis is restricted to children of the household head and spouse. 20 This is the approach used byBanerjee et al (2015) in evaluating the effect of poverty graduation programs across six different countries on a range of outcomes Ajayi and Ross (2017). who are not evaluating a randomized control trial modify this standardization approach to use with a difference-in-difference empirical identification strategy that does not have a randomly assigned control group.…”
mentioning
confidence: 99%
“…A study by Zins and Weill (2016) on determinants of financial inclusion in Africa found that additional education was associated with greater use of formal financial services. Other studies have affirmed this, finding that higher educated individuals tend to be more financially included (Kehinde and Phillip, 2018;Allen et al, 2016;Fung a cov a and Weill, 2015). In this study, education was measured by years of formal education of the household head.…”
Section: Farm and Household Characteristicsmentioning
confidence: 84%